Lean on me [videorecording (DVD)] - Avildsen, John G., 1935-2017; Freeman, Morgan; Guillaume, Robert; Todd, Beverly, 1946- (Distributed by Warner Home Video, 2010)
Based on the true story of New Jersey high school principal Joe Clark, who wins the support and respect of his students for his controversial methods in ridding the school of violent students and drug dealers.